Analytical method development and determination of hydrocortisone acetate and fusidic acid simultaneously in cream formulation, by reversed‐phase HPLC. (27th October 2020) - Rasool, Nawaz; Kanwal, Qudsia; Waseem, Muhammad; Mehrunnisa; Khan, Muhammad Irfan
Abstract: In this study, an accurate, simple, economical, precise and reproducible reversed‐phase HPLC method was developed for the estimation of fusidic acid and hydrocortisone acetate, according to the International Conference on Harmonization guidelines, in a cream formulation. Chromatographic separation was achieved by isocratic elution, on a Shimadzu reversed‐phased high‐pressure liquid chromatography instrument, equipped with a C18 column (150 × 4.6 mm, 5 μm) and UV detector at 225 nm wavelength, using acetonitrile and 0.05% trifluoroacetic acid (60:40), as a mobile phase and diluent, at flow rate 2 ml/min and an injection volume of 20 μl. The calibration curves were acquired with concentration range 80–120% and mean percentage recoveries for hydrocortisone acetate and fusidic acid were 100.14 and 100.81%, respectively. The limits of detection was obtained as 6.0667 and 6.807 μm ml −1 and the limits of quantification were 20.204 and 20.628 μm ml −1 for hydrocortisone acetate and fusidic acid, respectively. All of the validation parameters were within the acceptance criteria, as per International Conference on Harmonization requirements, for hydrocortisone acetate and fusidic acid. This method was found to be validated, simple, rapid and applicable for the simultaneous estimation of hydrocortisone acetate and fusidic acid by reversed‐phased high‐pressure liquid chromatography, for routine analytical testing in quality control, with a run time of 8 min.